Sign-changing solutions for Kirchhoff-type problems involving variable-order fractional Laplacian and critical exponents - Liang, Sihua; Molica Bisci, Giovanni; Zhang, Binlin (Nonlinear Analysis: Modelling and Control, 2022)
In this paper, we are concerned with the Kirchhoff-type variable-order fractional Laplacian problem with critical variable exponent. By using constraint variational method and quantitative deformation lemma we show the existence of one least energy solution, which is strictly larger than twice of that of any ground state solution.